2016
DOI: 10.1136/bmjopen-2015-010490
|View full text |Cite
|
Sign up to set email alerts
|

Social Autopsy of maternal, neonatal deaths and stillbirths in rural Bangladesh: qualitative exploration of its effect and community acceptance

Abstract: Objectives Social Autopsy (SA) is an innovative strategy where a trained facilitator leads community groups through a structured, standardised analysis of the physical, environmental, cultural and social factors contributing to a serious, non-fatal health event or death. The discussion stimulated by the formal process of SA determines the causes and suggests preventative measures that are appropriate and achievable in the community. Here we explored individual experiences of SA, including acceptan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…use of social autopsy can itself act as a social intervention helping communities to identify and work on health problems (Biswas et al, 2016). D'Ambrouso et al , for instance, have incorporated questions about the recognition of severity, access to, and quality of health services into the VA.…”
Section: (I)mentioning
confidence: 99%
“…use of social autopsy can itself act as a social intervention helping communities to identify and work on health problems (Biswas et al, 2016). D'Ambrouso et al , for instance, have incorporated questions about the recognition of severity, access to, and quality of health services into the VA.…”
Section: (I)mentioning
confidence: 99%
“…Community interaction enhances the ownership of the community, allows understanding of their own problems, and empowers the community to think and take appropriate action. Representative publicly-elected community leaders at the village level can change social barriers to prevent unwanted deaths, minimize delays and influence pregnant mothers to uptake care at government health facilities 46 , 47 .…”
Section: Impact Of the Systemmentioning
confidence: 99%
“…Ensuring the quality of data though conduction of verbal autopsy in the community and the best utilization of the findings at various level is also a challenge 40 – 42 . Moreover, social autopsy findings showed that social barriers are still a key issue in averting maternal and neonatal deaths 45 , 46 . It is recommended that social autopsy intervention in the community could play pivotal role in changing the beliefs and practices of the community to seek appropriate care during pregnancy, delivery and postpartum period.…”
Section: Challenges Aheadmentioning
confidence: 99%
“…All of these decisions are implemented and monitored by community leaders along with the members of local government. Community members also make a commitment to try and prevent any other future deaths [ 19 ].…”
Section: Opportunities and Challengesmentioning
confidence: 99%